Kritika : essays on intellectual property. - Ullrich, Hanns, 1939-; Drahos, Peter, 1955-; Ghidini, Gustavo, 1941- (Edward Elgar Publishing, 2018)
The fields of intellectual property have broadened and deepened in so many ways that commentators struggle to keep up with the ceaseless rush of developments and hot topics. Kritika: Essays on Intellectual Property is a series that is designed to help authors escape this rush. It creates a forum for authors who wish to more deeply question, investigate and reflect upon the evolving themes and principles of the discipline. This third volume of Kritika again brings together leading scholars from different fields and disciplines. Their essays reflect on some of the big problems in the field, addressing issues such as the way that institutions like WIPO continue with their propertization missions, how the bells of lobbyists toll incessantly for new data rights, and the ways in which discourses of human rights and information justice struggle to turn intellectual property from an instrument of private accumulation into one of service for the common good. Important questions in the field are also tackled; for example, how does the Islamic view of knowledge as life cohere with intellectual property, at a time when, as other essays show, intellectual property grounds new forms of state imperium? With contributions from: Sara Bannerman; Shamnad Basheer; Rahul Bajaj; Mohammed El Said; Blayne Haggart; Thomas Hoeren; P. Bernt Hugenholtz and Fiona Macmillan.